The Forgotten Subject. Subject Constitutions in Mediatized Everyday Worlds - Gentzel, Peter; Krotz, Friedrich; Wimmer, Jeffrey; Winter, Rainer (Palgrave Macmillan, 2023)
The volume provides a critical inventory of existing concepts of the subject in communication studies research. In addition, concepts are developed in order to be able to analyze subjectivity in the context of current theoretical debates (including media sociology, cultural studies, psychoanalysis, practice theory, science and technology studies) as well as social, cultural and technical developments (including digitalization, mediatization, mobility and networking). Since subject conceptions are of central importance for any communication and media analyses, the volume fills a central gap in communication and media studies.<br
Keywords: Subjectivity; Subject construction; Cultural Theory; Mediatization; Psychoanalysis; quantified self; Digitization; Practice Theory